Sulla legittimità dei provvedimenti del Governo a contrasto dell’emergenza virale da Coronavirus (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Coronavirus epidemic has triggered an emergency without precedent to which the Italian legal system has attempted to respond by resorting to extra-ordinem regulations. This essay intends to demonstrate how the government measures adopted are formally legitimate, given that they are founded on the principle of legality, in accordance with the Italian Constitution.
Keywords: CoViD-19; pandemic emergency; rule of law; extra-ordinem regulations; emergency legislation